IMPACT OF COGNITIVE-PSYCHOLOGICAL BARRIERS ON THE IMPLEMENTATION OF PEDAGOGICAL INNOVATION (World Bulletin of Social Sciences, 2023)
This article covers the features of the influence of cognitivepsychological barriers in the teacher on the creation, assimilation and implementation of pedagogical innovations
Keywords: cognitive-psychological barrier; implementation; pedagogical innovation